An Integrated Control Algorithm of ABS and DYC for Emergency Braking on a µ-Split Road - Chong Feng; Nenggen Ding; Yongling He (2012 International Conference on Control Engineering and Communication Technology, 2012)
An integrated control algorithm of antilock brake system (ABS) and direct yaw-moment control (DYC) using only the actuators of a conventional ABS but a few extra sensors is developed. The purpose of this algorithm is to maximize the utilization of road friction while maintaining directional stability of the vehicle during emergency braking on a μ-split road. An ABS algorithm based on slip ratio threshold is adopted. DYC is used to calculate the desired yaw moment, which is further used for determination of an adaptive modification coefficient for ABS control. The performance of the proposed integrated control algorithm is compared with modified independent control algorithm, independent control algorithm and low selection control algorithm of ABS via hardwire-in-the-loop (HIL) simulations. The results show that the comprehensive performance of the vehicle during emergency braking on a μ-split road is improved by employing the integrated control algorithm.